2016
DOI: 10.1177/0141076816661316
|View full text |Cite
|
Sign up to set email alerts
|

Change in plasma volume and prognosis in acute decompensated heart failure: an observational cohort study

Abstract: Objectives This study aimed to develop an inexpensive, readily available prognostic indicator in acute decompensated heart failure patients to guide management and improve outcome. Prognostic biomarkers for heart failure exist but are expensive and not routinely performed. Increasing plasma volume has been associated with worse outcomes. Setting UK University Teaching Hospital. Design Observational Cohort study. Participants 967 patients with acute decompensated heart failure. Methods Haemoglobin and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
(43 reference statements)
3
24
0
Order By: Relevance
“…Several studies have evaluated the prognostic value of formulas for the estimation of PV and PVS in ADHF patients. [14][15][16][17] Using data from the Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS), Duarte et al 14 examined the prognostic value of the PV, as estimated by the Strauss, Kaplan, and Hakim formulas. They found that of these 3 formulas, the strongest association was found between the estimated PV variation calculated by the Strauss formula and poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the prognostic value of formulas for the estimation of PV and PVS in ADHF patients. [14][15][16][17] Using data from the Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS), Duarte et al 14 examined the prognostic value of the PV, as estimated by the Strauss, Kaplan, and Hakim formulas. They found that of these 3 formulas, the strongest association was found between the estimated PV variation calculated by the Strauss formula and poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that decreased congestion, as manifested by hemoconcentration and a decrease in absolute PV, is associated with improved mortality [4,5,6,10,23]. This decrease in PV suggests that diuresis exceeds the rate of plasma refill from the extravascular space and is maintained over the period of decongestive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PV is generally well regulated in healthy individuals by complex signaling of neuroendocrine systems that maintain water and sodium homeostasis [1]. Any imbalance in the neurohormonal cascade can precipitate detrimental increases in PV in acute decompensated heart failure (ADHF) [2], leading to symptoms of congestion [3] and increased mortality [4,5,6]. These perturbations in PV may be corrected with diuresis, and the imbalance in the neurohormonal cascade attenuated by inhibitors of the renin-angiotensin-aldosterone system (RAAS).…”
Section: Introductionmentioning
confidence: 99%
“…The change in plasma volume can be used for prognostication in acute decompensated heart failure, and whole body plasma volume loss may be one of the possible mechanisms for the beneficial effects of SGLT2 inhibitors for cardiovascular diseases 17,18) . The Strauss-Davis-Rosenbaum formula is an easily accessible marker of estimating the percentage change in plasma volume in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…All participants completed a 12 h overnight fast before the CMT, as previously described 17) . Briefly, the cookie was ingested with water within a 20 min period, and blood samples for PG, IRI, and TG measurement were obtained at 0, 1, and 2 h after the participant had ingested half the volume of the cookie.…”
Section: Cookie Meal Testmentioning
confidence: 99%